2011
DOI: 10.1007/7854_2011_162
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Diagnostic Criteria for Alcohol Dependence with Genetic Animal Models

Abstract: A diagnosis of alcohol dependence (AD) using the DSM-IV-R is categorical, based on an individual’s manifestation of three or more symptoms from a list of seven. AD risk can be traced to both genetic and environmental sources. Most genetic studies of AD risk implicitly assume that an AD diagnosis represents a single underlying genetic factor. We recently found that the criteria for an AD diagnosis represent three somewhat distinct genetic paths to individual risk. Specifically, heavy use and tolerance versus wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 126 publications
0
18
0
Order By: Relevance
“…www.nature.com/scientificreports www.nature.com/scientificreports/ These concentrations were chosen to ensure sedation, which is reported to occur at >2.5 g/kg of alcohol 41 . Both groups of WT and KO mice had similar latency to onset of LORR (Fig.…”
Section: Increased Reward Potency Of Alcohol By Nbcn1 Lossmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ These concentrations were chosen to ensure sedation, which is reported to occur at >2.5 g/kg of alcohol 41 . Both groups of WT and KO mice had similar latency to onset of LORR (Fig.…”
Section: Increased Reward Potency Of Alcohol By Nbcn1 Lossmentioning
confidence: 99%
“…Alcohol-dependent disorders have been extensively studied in rodents but the human disorder is not fully mimicked by these models (Crabbe et al, 2013 ). A few studies have been conducted on post-mortem brain samples from alcoholics (Lewohl et al, 1997 , 2001 ; Dodd and Lewohl, 1998 ; Buckley et al, 2000 , 2006 ; Mayfield et al, 2002 ; Buckley and Dodd, 2004 ; Dodd et al, 2004 ; Flatscher-Bader et al, 2005 , 2006 ; Kalsi et al, 2009 ; Jin et al, 2011a , 2014a , b ; Domart et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory animals have been used to model various aspects of the addictive process and such studies have shown substantial genetic variability across many phenotypes hypothesized to be important (Crabbe, 2008; Crabbe, Kendler & Hitzemann, 2013; Crabbe & Phillips, 2004). One phenotype domain of particular interest comprises the reinforcing/rewarding and punishing/aversive effects of ethanol, reflecting the belief that vulnerability to addiction depends, in part, on genetic variation in sensitivity to these effects (Tabakoff & Hoffman, 1988).…”
mentioning
confidence: 99%